Can combine headers and travel speeds affect the quality of soybean harvesting operations? - Menezes, Patricia C. de; Silva, Rouverson P. da [UNESP]; Carneiro, Franciele M. [UNESP]; Girio, Lucas A. da S. [UNESP]; Oliveira, Mailson F. de [UNESP]; Voltarelli, Murilo A. (Univ Federal Campina Grande, 2018)
Assuring the quality of mechanical soybean harvesting is crucial to ensure that investment in other stages of crop production is converted into profit for the farmer. Because the quality of this operation is related to decreased losses, which may be affected by the combine header used and by the harvesting speed, the aim of the present study was to assess the quality of mechanical soybean harvesting in the Southern Cone of Rondonia, using harvesters with different combine headers and travel speeds via statistical process control. The experiment was performed during the 2015/16 harvest in an agricultural area of the municipality of Cabixi, RO, located at the geographical coordinates 13 degrees 27'S and 60 degrees 41'W. The study was designed based on the premises of the statistical process control, sampling 80 points 100 m apart. Combine header, internal, total, and cutting height losses were assessed. Quality of the harvesting process was assessed using the draper header. Travel speed had little effect on process quality. Crop losses were higher than the acceptable limit, indicating the need to improve the process.
Keywords: statistical process control; harvester; Glycine max; losses; combine header